The Role of Teachers in Developing the Discipline in Children Aged 4-5 Years - Ipas Pasohah; Atin Fatimah (CV. Rayyan Dwi Bharata, 2023)
The role of the teacher is that of a professional educator with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education in formal channels, basic education, and secondary education. Discipline in children can include teaching, guidance or encouragement carried out teacher to his son. Applying discipline to children aims to make children study well and children achieve optimal growth and development. The research used is using qualitative methods on the grounds that this qualitative research is able to capture the symptoms that accompany a problem in detail and as it is. Qualitative research is a research aimed at describing and analyzing phenomena, events, social activities, and attitudes of people individually the principles and explanations that lead to conclusions. The teacher guides children during habituation in activities. The teacher gives guidance to children who do not take part in the line, the teacher demands the children to line up with their friends and tidy up the children in the line, after that the teacher gives praise to the children who have joined the line in the school yard. the teacher as a trainer in developing discipline, namely the teacher practices through daily learning activities. the role of the teacher in developing the discipline of children aged 4-5 years in Kindergarten Kasih Bunda Baros is that by developing the character of discipline seen from the teacher's role as a guide and coach towards children can instill positive disciplinary character values that will stick in the future until the child is an adult.